Cyclic di-AMP as endogenous adjuvant enhanced BCG-induced trained immunity and protection against Mycobacterium tuberculosis in mice - Ning, Huanhuan; Kang, Jian; Lu, Yanzhi; Liang, Xuan; Zhou, Jie; Ren, Rui; Zhou, Shan; Zhao, Yong; Xie, Yanling; Bai, Lu; Zhang, Linna; Kang, Yali; et al. (Frontiers in Immunology, 2022)
Bacillus Calmette-Guérin (BCG) is a licensed prophylactic vaccine against tuberculosis (TB). Current TB vaccine efforts focus on improving BCG effects through recombination or genetic attenuation and/or boost with different vaccines. Recent years, it was revealed that BCG could elicit non-specific heterogeneous protection against other pathogens such as viruses through a process termed trained immunity. Previously, we constructed a recombinant BCG (rBCG-DisA) with elevated c-di-AMP as endogenous adjuvant by overexpressing di-adenylate cyclase of Mycobacterium tuberculosis DisA, and found that rBCG-DisA induced enhanced immune responses by subcutaneous route in mice after M. tuberculosis infection. In this study, splenocytes from rBCG-DisA immunized mice by intravenous route (i.v) elicited greater proinflammatory cytokine responses to homologous and heterologous re-stimulations than BCG. After M. tuberculosis infection, rBCG-DisA immunized mice showed hallmark responses of trained immunity including potent proinflammatory cytokine responses, enhanced epigenetic changes, altered lncRNA expressions and metabolic rewiring in bone marrow cells and other tissues. Moreover, rBCG-DisA immunization induced higher levels of antibodies and T cells responses in the lung and spleen of mice after M. tuberculosis infection. It was found that rBCG-DisA resided longer than BCG in the lung of M. tuberculosis infected mice implying prolonged duration of vaccine efficacy. Then, we found that rBCG-DisA boosting could prolong survival of BCG-primed mice over 90 weeks against M. tuberculosis infection. Our findings provided in vivo experimental evidence that rBCG-DisA with c-di-AMP as endogenous adjuvant induced enhanced trained immunity and adaptive immunity. What’s more, rBCG-DisA showed promising potential in prime-boost strategy against M. tuberculosis infection in adults.